INTEGRASI EFISIENSI, KEADILAN DAN KEBERKAHAN DALAM ALOKASI PENDAPATAN PERSPEKTIF MAQASID AL-SYARI’AH - Wardah Mujadidah Hananiyah; Mahyudin Mahyudin; Nonie Afrianty (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2025)
Integration of efficiency, justice, and blessing in income allocation based on the perspective of Maqasid al-Syari'ah. In Islamic economics, income allocation is not solely oriented towards increasing material profits, but must also be based on just spiritual and social values. This study uses a qualitative approach with a descriptive-analytical research type. The descriptive-analytical approach is used to systematically describe the concepts of efficiency, justice, and blessing, and analyze their relationship with the main objectives of sharia (maqasid al-shari'ah). The results of the analysis show that Maqasid Al-Syari'ah, especially the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), descendants (hifz al-nasl), and property (hifz al-mal), provides ethical principles that bind the concepts of efficiency and justice. In this perspective, efficiency is not only measured by maximizing output or material profit, but also by its contribution to achieving comprehensive welfare (falah). Meanwhile, justice ('adl) is realized through allocation that ensures the fulfillment of basic needs for all parties and minimizes inequality. This integration is achieved through the concept of blessing, which serves as an indicator of the spiritual and material success of income allocation. Blessings emphasize the moral and social dimensions in the use of wealth, encouraging practices such as zakat, almsgiving, and social investment that are oriented towards long-term benefits (maslahah).